Digital Marketing sebagai Upaya Mempeluas Pasar Pasa Sentra Mocaf Desa Bolo Kecamatan Kare Madiun - Febrilyantri, Candra; Amanah, Siti Nur; Aldarisma, Meisyavani; Adli, Muhammad Saiful; Wibowo, Firnanda (Civiliza Publishing, 2024)
Healthy living has been widely realized by the community, so that many people in addition to starting exercise also switch to consuming healthy food. One of them is healthy eating produced from Mocaf (Modified Cassava Flour) raw materials. This flour is widely produced in Bolo Village, Kare District, Madiun Regency, East Java. However, there is a problem after observation in the field, namely the lack of marketing in reaching the wider community, even though outside the Madiun area, this flour is increasingly in demand. This service uses the ABCD (Asset Based Community Development) method, which is a method that utilizes the assets and potential around and owned by youth or communities in the community. There are five stages in the ABCD method, namely inculturation, discovery, design, define, reflection. Efforts to expand the marketing network were carried out by conducting a digital marketing semibar work program and mentoring afterwards. The evaluation results showed that with the increase in digital marketing literacy, marketing became wider.